Image encryption using vigenere cipher with bit circular shift - Susanto, Arief; Khotimah, Tutik; Taufik Sumadi, Muhammad; Warsito, Joko; ., Rihartanto (International Journal of Engineering and Technology, 2018)
Cryptography is a method of securing text data, images and sound in order to secure its confidentiality and to minimize data stealing, attack, etc. The purpose of this study is to improve classic Vigenere cipher using bit circular shift on image encryption. This experiment uses both RGB and grayscale images as samples and shows that Vigenere cipher with bit circular shift has better performance when encrypting an image both visually and its randomness. It is obtained the MAE values of images of final encryption process are 81.702637 of RGB and 73.678756 of grayscale, and the final decryption process of 0 for both images. The randomness of images of the final encryption process is shown by its correlation coefficient values; it is 0.033857 of RGB and -0.058501 of grayscale.